Needs Analysis: Interactive Problem-Based Learning Media Assisted by Google Sites in Commercial Accounting Material - Daniati, Daniati; Jaenudin, Riswan; Safitri , Erna Retna (Journal of Educational Sciences, 2025)
This study aims to analyse the need for Google Sites-assisted problem-based interactive learning media in Trading Company Accounting materials at SMKN 1 Pedamaran Timur. The research background is based on learning conditions that are still dominated by the use of conventional media, such as transaction document sheets and simple visual presentations, so that learning outcomes are not optimal. The research method used was qualitative descriptive with data collection techniques through observation, interviews, documentation, and questionnaires to 35 students and 5 Accounting teachers. The results of the analysis showed that the students' needs for learning media were in the high category with a percentage of 81.67%, while the needs of teachers were in the high category with a percentage of 82%. These findings indicate the need for innovative, practical, and contextual learning media to improve student learning outcomes. Therefore, the development of interactive learning media based on Google Sites assisted by Google Sites is expected to be a solution to support the Accounting learning process of Trading Companies that is more effective, interesting, and in accordance with the demands of the Independent Curriculum.